Preparation of Silica Aerogel and Its Adsorption Performance to Organic Molecule - Hong-xin Shi; Jing-tao Cui; Hai-min Shen; Hong-ke Wu (Advances in Materials Science and Engineering)
Hydrophobic and lipophilic silica aerogel was prepared from water-glass by gelling, aging, silylation, and drying under atmospheric pressure and characterized by FT-IR and SEM. The effect of preparation process on aerogel density and the aerogel density on contact angle of water on it were investigated in detail. pH 6 is most beneficial to shorten gelling time and to obtain the lowest density of silica aerogel. Increasing TEOS concentration of aging solution to 25 v% could decrease aerogel density to 0.093 g/cm3. The silica aerogel exhibits good hydrophobicity even though its density is 0.30 g/cm3. There are few changes in their adsorption capacities after 3 cycles of adsorption-desorption. The adsorption performance of the silica aerogel to organic solvent in water is different from in pure solvents. The critical surface tension (γC) of the silica aerogel prepared here is about 30.8 mN/m. If the surface tension of aqueous solvent solution (γ) is greater than γC, it will wet the aerogel surface partially. If γ  ≤  γC, the solution will wet all aerogel surface and be adsorbed well. This work delivers us a method to adsorb solvents from their waste water by adjusting the surface tension of the waste water to lower than γC of the adsorbent.